2019
DOI: 10.18592/al-banjari.v18i1.2532
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi Dan Sikap Masyarakat Terhadap Wisata Syariah (Halal Tourism) Di Pulau Santen Kabupaten Banyuwangi

Abstract: Sharia / halal tourism tourism is a trend and golden opportunity for the region. Banyuwangi as one of the regions that has natural resources such as coastal, sea, and small islands trying to develop the tourism sector located in Santen Island, Karangrejo Banyuwangi Village with sharia tourism forms. The aim of the research is to find out how the perceptions and attitudes of the community towards the existence of sharia tourism (halal tourism) in Banyuwangi Regency. The research methods used in this study are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Dimana pada tahun 1967 telah dilaksanakan konferensi di Cordoba, Spanyol oleh World Tourism Organization (UNWTO) dengan judul "Tourism and Religions: Contribution to the Dialogue of Cultures, Religions and Civilizations". Wisata ziarah meliputi aktivitas wisata yang didasarkan atas motivasi nilai religi tertentu seperti Hindu, Budha, Kristen, Islam, dan religi lainnya (Fawaid & Khotimah, 2019). Seiring waktu, fenomena wisata tersebut tidak hanya terbatas pada jenis wisata ziarah atau religi tertentu, namun berkembang ke dalam bentuk baru nilai-nilai yang bersifat universal seperti kearifan lokal, memberi manfaat bagi masyarakat, dan unsur pembelajaran.…”
Section: Pendahuluanunclassified
“…Dimana pada tahun 1967 telah dilaksanakan konferensi di Cordoba, Spanyol oleh World Tourism Organization (UNWTO) dengan judul "Tourism and Religions: Contribution to the Dialogue of Cultures, Religions and Civilizations". Wisata ziarah meliputi aktivitas wisata yang didasarkan atas motivasi nilai religi tertentu seperti Hindu, Budha, Kristen, Islam, dan religi lainnya (Fawaid & Khotimah, 2019). Seiring waktu, fenomena wisata tersebut tidak hanya terbatas pada jenis wisata ziarah atau religi tertentu, namun berkembang ke dalam bentuk baru nilai-nilai yang bersifat universal seperti kearifan lokal, memberi manfaat bagi masyarakat, dan unsur pembelajaran.…”
Section: Pendahuluanunclassified
“…Therefore, it is important to take into account the diversity of people's perspectives, experiences, and assessments. This condition has at least some similarities with people's perceptions in Pekanbaru and Padang, both of which have high ratings (Putriana & Rimer, 2019), Lombok (Susanty, 2020), Banyuwangi (Fawaid & Khotimah, 2019), and Nusa Tenggara Barat (Permadi, Darwini, Retnowati, Negara, & Septiani, 2018).…”
Section: Discussionmentioning
confidence: 74%
“…The coefficient value on the perception variable is 0.325, meaning that if public perception increases, it will increase the development of halal tourism by 0.325.The results of this study are also in line with researchSaifuddin and Mukarromah (2021) His research explains the good public perception of the application of sharia tourism. Creating a good public perception will make Indonesia an attractive sharia tourism destination.In addition,Fawaid and Khotimah (2019) in their research, they found that public perception of sharia tourism was positive, namely 75%. A good influence between public perception and sharia tourism is alsofound in research Putriana (2019).…”
mentioning
confidence: 89%